O reconhecimento do status de refugiado ambiental: um problema conceitual? - Peixer, Janaína Freiberger Benkendorf (2017)
It analyses international legal instruments concerning refugees to seek answers about the protection for climate refugees. It happens because Geneva Convention of 1951 does not contemplate climate change issue among the list of protection. The debates about the broadly use of the term lies under the possible weakness of the refugees institute.